The Social Context of Street Culture in Substance Use; a Literature Review of Homeless Youth Perspectives - Wilson, Cate; Bradbury, Joanne (International Journal of Medical and Health Sciences Research, 2015)
Homeless youth experience disproportionately high rates of psychological problems and substance-related disorders. Street culture provides protection and support for young people who find themselves excluded from family and socialising institutions. The aim of this review is to examine the social context of the street culture and substance use from the perspective of homeless youth. Databases searched included Cochrane, Cinahl, Medline, and PsychINFO. Search terms included homeless, youth and substance use. Twenty studies (12 quantitative and 8 qualitative) were identified. Major themes included survival and adaption to the street culture, social and human capital gains, and social networks. Street youth viewed substances as helpful for treating physical and psychological problems, and as a means of generating social capital necessary for survival in the street culture. Intervention programs should not only address the trauma and mental health issues of young people but also the context of the substance-using street culture.